Electromagnetic Navigation-Guided Radiofrequency Thermocoagulation in Trigeminal Neuralgia: Technical Note with Three Case Reports - Chen, Min-Jie; Gu, Li-Xu; Zhang, Wei-Jie; Yang, Chi; Dong, Min-Jun (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objective To introduce our device and procedure of electromagnetic navigation (EMN)-guided radiofrequency thermocoagulation (RFT) in patients with trigeminal neuralgia (TN).Methods The EMN system mainly consists of an electromagnetic localizer, a thermoplastic facial mask with fiducial markers, and navigation software. A new surgical interface in which the foramen ovale (FO) and the trigeminal ganglion (TG) were integrated was used. It was applied in three patients with TN.Results FO was successfully and accurately cannulated on the first attempt by using EMN guidance. During the follow-up period, pain did not reoccur, and appropriate trigeminal sensory paresthesia was elicited. There were no surgery-related complications.Conclusion The EMN system is effective and highly accurate for RFT in patients with primary TN. Our modification of the registration system and surgical interface could make the RFT process more simple and accurate.
Keywords: electromagnetic navigation; radiofrequency thermocoagulation; thermoplastic facial mask; image fusion